Exploration of the Existence Forms and Patterns of Dissolved Oxygen Molecules in Water - Yuan, Hewei; Zhang, Yaozhong; Huang, Xiaolu; Zhang, Xiwu; Li, Jinjin; Huang, Yufeng; Li, Kun; Weng, Haotian; Xu, Yang; Zhang, Yafei (Nano-Micro Letters, 2024)
The structure of liquid water is primarily composed of three-dimensional networks of water clusters formed by hydrogen bonds, and dissolved oxygen is one of the most important indicators for assessing water quality. In this work, distilled water with different concentration of dissolved oxygen were prepared, and a clear negative correlation between the size of water clusters and dissolved oxygen concentration was observed. Besides, a phenomenon of rapid absorption and release of oxygen at the water interfaces was unveiled, suggesting that oxygen molecules predominantly exist at the interfaces of water clusters. Oxygen molecules can move rapidly through the interfaces among water clusters, allowing dissolved oxygen to quickly reach a saturation level at certain partial pressure of oxygen and temperature. Further exploration into the mechanism by molecular dynamics simulations of oxygen and water clusters found that oxygen molecules can only exist stably at the interfaces among water clusters. A semi-empirical formula relating the average number of water molecules in a cluster (n) to 17O NMR half-peak width (W) was summarized: n = 0.1 W + 0.85. These findings provide a foundation for exploring the structure and properties of water. Highlights: 1 A clear negative correlation between the size of water clusters and the concentration of dissolved oxygen was observed. This implied that smaller clusters water exhibits higher concentrations of dissolved oxygen. 2 Oxygen molecules are primarily existed at the surfaces or interfaces of water clusters and can rapidly traverse the gas liquid interface. 3 A semi empirical formula relating the average number of water molecules in a cluster to 17O NMR half peak width was derived, demonstrating an approximate lin ear relationship.